Socialno delo z ranljivo mladostnico v vzgojno- izobraževalni ustanovi - Paladin, Stjepan (Socialno delo, 2024)
The life of young people is examined and the impact of individual factors of growing up explained, including protective factors or risk factors for vulnerable young people. In relation to a vulnerable female adolescent ex- amined in the paper, the gender-, family-, school and peer-related factors had a negative impact on her life, as her emotional, behavioural and mental problems gradually exacerbated. Throughout years, the adolescent’s problems gradually led to different disorders and manifested themselves in several areas of life, to the extent where they started threatening her life. In her case, auto-aggressive behaviour with severe forms of self-injury and suicide attempts prevailed. The adolescent underwent holistic treatment provided by a multidisciplinary expert team. The qualitative analysis showed that prevention, early detection and appropriate action are key measures in case of family violence and essential for a child’s optimal psychosocial and mental development in their developmental period. The analysis of interviews conducted with professional workers showed that a social worker included into a multidisciplinary team is one of its important experts, as they have a crucial role in working with and providing support to families facing numerous challenges.
Keywords: case study; dejavniki tveganja; growing up; mladi; multidisciplinarni tim; multidisciplinary team; odraščanje; risk factors; študija primera; teamwork; timsko delo; young people